Cationic mixed electrolyte of zinc capacitor, preparation method of cationic mixed electrolyte and aqueous zinc capacitor

By designing a cationic mixed electrolyte containing ammonium salt and zinc salt in an aqueous zinc mixed capacitor, the cation adsorption behavior on the surface of the carbon cathode is regulated, and the problem of low energy density of the carbon cathode is solved, and the energy storage effect of high energy density and long cycle life is achieved.

CN119786278AActive Publication Date: 2025-04-08TONGJI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411772095.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-08
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The carbon cathodes of existing aqueous zinc hybrid capacitors have a problem of low energy density, which is mainly due to the insufficient zinc-eleolyte activity in the carbon cathode-electrolyte world and the unsustainable adsorption process hindering the further improvement of capacitor performance.

Method used

A cationic mixed electrolyte of zinc capacitor is designed, including ammonium salt, zinc salt and deionized water as solvents. By adjusting the ratio of ammonium salt and zinc salt, the cation adsorption behavior on the carbon cathode surface is regulated, and the Helmholtz plane reconstruction is induced to realize the reallocation of space charge.

Benefits of technology

It significantly reduces the interfacial electron and ion transport impedance, improves the reaction activity and reaction kinetics of the carbon cathode, and realizes energy storage with high energy density and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786278A_ABST
    Figure CN119786278A_ABST
Patent Text Reader

Abstract

The invention provides a cationic mixed electrolyte of a zinc capacitor, a preparation method of the cationic mixed electrolyte and an aqueous zinc capacitor, and belongs to the technical field of zinc capacitors. The cation mixed electrolyte of the zinc capacitor comprises ammonium salt, zinc salt and a solvent, and the solvent is deionized water. The preparation method of the cation mixed electrolyte of the zinc capacitor comprises the following steps: step 1, weighing a zinc salt and an ammonium salt in a certain molar ratio; and 2, adding a zinc salt and an ammonium salt into water, uniformly stirring, performing ultrasonic treatment to obtain a clear solution, and standing to obtain the cation mixed electrolyte of the zinc capacitor. The graded solvation structure in the cation mixed electrolyte of the zinc capacitor is beneficial to reconstruction of a Helmholtz layer on the surfaces of the cathode and the electrolyte, redistribution of space charges is realized, interface electron and ion transmission impedance is remarkably reduced, the reaction activity and the reaction kinetics process of the carbon cathode are improved, and the service life of the cathode is prolonged. Energy storage with high energy density and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc capacitors, and in particular relates to a cationic mixed electrolyte of a zinc capacitor, a preparation method thereof and an aqueous zinc capacitor. Background Art

[0002] Aqueous zinc hybrid capacitors have recently become a highly competitive energy storage system due to their combination of the dual advantages of battery-type zinc anodes and supercapacitor-type carbon-based cathodes. The reversible deposition / stripping behavior of the zinc anode and the high theoretical mass specific capacity (820 mAh g -1 ) and suitable redox potential (-0.76V relative to standard hydrogen electrode), provide sufficient charge and guarantee for the development of high-energy and long cycle life aqueous zinc hybrid capacitors. Therefore, the current goal is mainly focused on promoting the research of high-performance cathode materials for aqueous zinc hybrid capacitors, mainly focusing on the development of carbon nanomaterials with high specific surface area. However, the developed carbon cathodes still have the problem of low energy density, because the inherent zinc affinity activity and unsustainable adsorption behavior of the carbon cathode-electrolyte interface hinder the further improvement of the performance of aqueous zinc hybrid capacitors. In order to cope with these problems, the key breakthrough lies in the design of a highly electroactive and stable cathode electrolyte interface to achieve more efficient charge storage.

[0003] The capacitive energy storage of carbon cathodes mainly relies on the double-layer energy storage mechanism, which depends largely on the specific surface area and the distribution of charge carriers in the electrolyte. A large specific surface area can effectively expand the electrode / electrolyte contact and thus improve the capacity of the carbon cathode. However, the specific surface area of ​​the carbon cathode is difficult to increase indefinitely, and is accompanied by negative effects such as poor pore utilization caused by the mismatch between the charge carrier and pore structure size, resulting in limited capacity enhancement of carbon cathode materials. The size and solvation structure of the charge carriers significantly affect the interfacial electrochemical behavior and the double-layer energy storage mechanism. Charge carriers play a vital role in regulating the dynamic charge transfer and spatial storage at the carbon cathode interface, among which high-density interfacial charges are conducive to increasing the capacity of the carbon cathode.

[0004] Therefore, rationally designing the charge carrier solvation structure in the electrolyte and regulating the spatial distribution of charge carriers at the cathode-electrolyte interface are particularly critical for effective charge storage. Summary of the invention

[0005] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a cationic mixed electrolyte for zinc capacitors, a preparation method thereof and an aqueous zinc capacitor.

[0006] The invention provides a cationic mixed electrolyte for a zinc capacitor, which has the following characteristics and comprises: an ammonium salt, a zinc salt and a solvent, wherein the solvent is deionized water.

[0007] In the cationic mixed electrolyte of the zinc capacitor provided by the present invention, it can also have the following characteristics: wherein, the ammonium salt is any one of ammonium trifluoromethanesulfonate, sulfuric acid and ammonium acetate, and the zinc salt is any one of zinc trifluoromethanesulfonate, zinc sulfate and zinc acetate.

[0008] The cationic mixed electrolyte of the zinc capacitor provided by the present invention may also have the following characteristics: wherein the concentration of the ammonium salt and the zinc salt in the cationic mixed electrolyte of the zinc capacitor is 0.1-2 mol / L.

[0009] The cationic mixed electrolyte of the zinc capacitor provided by the present invention may also have the following characteristics: wherein the molar ratio of the ammonium salt to the zinc salt is 1:5-5:1.

[0010] The present invention also provides a method for preparing a cationic mixed electrolyte for a zinc capacitor, which has the following characteristics and is used to prepare the above-mentioned cationic mixed electrolyte for a zinc capacitor, comprising the following steps: step 1, weighing a zinc salt and an ammonium salt in a certain molar ratio; step 2, adding the zinc salt and the ammonium salt into water, stirring evenly, ultrasonically obtaining a clear solution, and letting it stand to obtain the cationic mixed electrolyte for the zinc capacitor.

[0011] The method for preparing the cationic mixed electrolyte of the zinc capacitor provided by the present invention may also have the following characteristics: wherein, in step 2, the mixing method is ultrasonic for 2 hours and the standing time is 24 hours.

[0012] The present invention also provides an aqueous zinc capacitor, which has the following characteristics: the cationic mixed electrolyte of the zinc capacitor is used.

[0013] The aqueous zinc capacitor provided by the present invention may also have the following characteristics: wherein the positive electrode material of the aqueous zinc hybrid capacitor is a porous carbon material, the negative electrode material is zinc, and the cationic mixed electrolyte is a cationic mixed electrolyte of a zinc capacitor. When the cationic mixed electrolyte of a zinc capacitor is used in an aqueous zinc capacitor, the graded cationic solvation structure induces the Helmholtz plane reconstruction of the carbon cathode surface and thereby affects the spatial charge distribution. The synergistic effect of the cationic mixed electrolyte regulates the interfacial adsorption behavior and electrochemical properties of the zinc capacitor.

[0014] The aqueous zinc capacitor provided by the present invention may also have the following characteristics: the cation adsorption behavior on the carbon cathode surface is regulated by adjusting the ratio of ammonium salt to zinc salt, the hydrated cations of ammonium have a smaller size than the hydrated cations of zinc, and the graded cation mixed electrolyte can regulate the Helmholtz plane of the cathode surface.

[0015] Functions and Effects of the Invention

[0016] According to the cationic mixed electrolyte of the zinc capacitor involved in the present invention, the preparation method thereof and the aqueous zinc capacitor, because the cationic mixed electrolyte of the zinc capacitor includes an ammonium salt, a zinc salt and a solvent, the solvent is deionized water. In the present invention, the concentration range of the electrolyte salt in the electrolyte is 0.1-2 mol / L, and the molar ratio of the ammonium salt to the zinc salt is 1:5-5:1-. By adjusting the ratio of the ammonium salt and the zinc salt to regulate the cation adsorption behavior on the surface of the carbon cathode, the hydrated cation of ammonium has a smaller size than the hydrated cation of zinc, and the graded cationic mixed electrolyte can regulate the Helmholtz plane of the cathode surface, realize the redistribution of spatial charge, significantly reduce the interface electron and ion transfer impedance, improve the reaction activity and reaction kinetics of the carbon cathode, and store energy with high energy density and long cycle life.

[0017] In addition, the raw materials of the cationic mixed electrolyte of the zinc capacitor of the present invention are widely available and have low cost.

[0018] The preparation method of the cationic mixed electrolyte of the zinc capacitor of the present invention is: zinc salt and ammonium salt of a certain molar ratio are added into water and mixed evenly to obtain the cationic mixed electrolyte of the zinc capacitor. The preparation method is simple to operate and does not involve harmful reagents or vacuum preparation conditions.

[0019] Furthermore, because the electrolyte of the aqueous zinc capacitor of the present invention is a cation mixed electrolyte of the zinc capacitor of the present invention, the aqueous zinc capacitor has good performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the mechanism of action of the cationic mixed electrolyte of the zinc capacitor in Example 1 of the present invention;

[0021] Figure 2 The conductivity performance test diagram of the electrolyte prepared in Example 1 of the present invention and Comparative Example 1 and Comparative Example 2 is shown in FIG.

[0022] Figure 3 It is a performance diagram of electrochemical impedance test in the electrolyte prepared in Example 1 of the present invention and Comparative Example 1 and Comparative Example 2;

[0023] Figure 4 It is a performance test diagram of differential capacitance curves in the electrolytes prepared in Example 1 of the present invention and Comparative Examples 1 and 2;

[0024] Figure 5 is a graph showing the distribution of micelle particle sizes in the electrolytes prepared in Example 1 of the present invention and Comparative Examples 1 and 2;

[0025] Figure 6It is a CV curve performance test diagram of the zinc capacitor in the electrolyte prepared in Example 1 of the present invention and Comparative Example 1 and Comparative Example 2 under the test condition of 2mV / s;

[0026] Figure 7 It is a rate performance test diagram of a zinc capacitor of an electrolyte prepared in Example 1 of the present invention and an electrolyte prepared in Comparative Example 1 and Comparative Example 2 at 25° C.;

[0027] Figure 8 This is a test graph of the cycle performance of a zinc capacitor of the electrolyte 1M Zn(OTF)2+1M NH4OTF prepared in Example 1 of the present invention at a charge and discharge current density of 30A / g. DETAILED DESCRIPTION

[0028] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the following examples are combined with the accompanying drawings to specifically describe the cationic mixed electrolyte of the zinc capacitor of the present invention, its preparation method and the aqueous zinc capacitor.

[0029] <Example 1>

[0030] The present embodiment provides a cationic mixed electrolyte for a zinc capacitor, wherein the cationic mixed electrolyte for a zinc capacitor comprises: 1M zinc trifluoromethanesulfonate, 1M ammonium trifluoromethanesulfonate and water.

[0031] This embodiment also provides a method for preparing the cationic mixed electrolyte of the zinc capacitor, the preparation method comprising the following steps:

[0032] Step 1: Accurately weigh 1 mol of zinc trifluoromethanesulfonate and 1 mol of ammonium trifluoromethanesulfonate.

[0033] Step 2: Add the above zinc trifluoromethanesulfonate and ammonium trifluoromethanesulfonate into water, stir evenly, dilute to a desired concentration, and then let stand to obtain a cationic mixed electrolyte for a zinc capacitor.

[0034] This embodiment also provides an aqueous zinc capacitor, wherein the positive electrode of the aqueous zinc capacitor is a graded porous carbon material, the electrolyte is a cationic mixed electrolyte of the zinc capacitor prepared in this embodiment, the negative electrode is a metal zinc sheet (purity ≥ 99.99%), and the capacitor is assembled using a GE-Whatman glass fiber diaphragm.

[0035] The preparation process of the positive electrode of the aqueous zinc capacitor is as follows:

[0036] ZnCl2 (3.0 g) was dissolved in a solvent mixture consisting of ethanol (30 mL), deionized water (50 mL), ammonium hydroxide (25–28%, 12 mL) and N, dimethylformamide (DMF, 30 mL). 1H-1,2,3-triazole (4 mL) was then added dropwise to the mixed solution and stirred at room temperature for 12 h, and then the obtained white product was filtered, washed, and finally dried at 80 ° C for 12 h to obtain a white precursor powder. The synthesized precursor was calcined at 800 ° C for 2 h at a heating rate of 2 ° C in a nitrogen environment. The carbonized sample was washed with 4 M salt solution for 4 h to remove the zinc component, then rinsed with water and dried at 80 ° C for 24 h. The obtained graded porous carbon material: 60wt% polytetrafluoroethylene emulsion (purchased from Shanghai San Ai Fu New Materials Co., Ltd.): acetylene black = 8:1:1 were mixed evenly in the following mass ratio, and then placed in an oven for drying. The dried sample was pressed onto a stainless steel mesh (purchased from Ningcong Silk Screen in Jiangsu Province) at a pressure of 20MPa, and vacuum dried at 100°C for 24h to obtain the positive electrode of the battery.

[0037] The energy storage performance of aqueous zinc capacitors was tested by CHI660E electrochemical workstation. The capacity retention rate of aqueous zinc capacitors after 400,000 cycles of charge and discharge was above 98.59%, showing excellent energy density and excellent cycle life.

[0038] Figure 1 Schematic diagram of the mechanism of action of the cationic mixed electrolyte of the zinc capacitor in Example 1 of the present invention.

[0039] like Figure 1 As shown, the cationic mixed electrolyte (1M Zn(OTF)2+1MNH4OTF cationic mixed electrolyte) of the zinc capacitor prepared in Example 1 can change the solvation structure of the cathode and electrolyte interface, so that its Helmholtz layer is reconstructed. Ammonium ions have smaller water and ionic radius and smaller desolvation energy, so they can provide a fast reaction kinetic process; and highly active zinc ions can form high-energy ionic bonds to provide high specific capacity for zinc ion capacitors. Based on the synergistic effect of the cationic mixed electrolyte, the specific capacity, rate performance and cycle stability of the zinc capacitor are simultaneously improved.

[0040] <Comparative Example 1>

[0041] In this comparative example, a 2M aqueous solution of ammonium trifluoromethanesulfonate was prepared as a cationic mixed electrolyte for a zinc capacitor as a comparative sample (in order to highlight the improvement of the electrolyte performance by the double cation in Example 1, the concentration of ammonium trifluoromethanesulfonate was set to 2M).

[0042] <Comparative Example 2>

[0043] In this comparative example, a 2M aqueous solution of zinc trifluoromethanesulfonate was prepared as a cation mixed electrolyte for zinc capacitors as a comparative sample (in order to highlight the improvement of the electrolyte performance by the double cation in Example 1, the concentration of ammonium trifluoromethanesulfonate was set to 2M).

[0044] <Test example>

[0045] The electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested for conductivity, electrochemical impedance, differential capacitance curve performance, micelle size distribution, CV curve performance of zinc capacitors, rate performance of zinc capacitors, and cycle performance of zinc capacitors. The zinc capacitors involved were replaced with corresponding electrolytes based on the aqueous zinc capacitors in Example 1.

[0046] Figure 2 It is a test graph of the conductivity performance of the electrolytes prepared in Example 1 of the present invention and Comparative Examples 1 and 2.

[0047] like Figure 2 As shown, due to the hierarchical solvation structure, the mixed cation electrolyte in Example 1 has higher ionic conductivity than the single cation electrolytes in Comparative Examples 1 and 2, and can perform excellent ion and electron conduction processes during electrochemical testing.

[0048] Figure 3 It is a performance diagram of electrochemical impedance test in the electrolyte prepared in Example 1 of the present invention and Comparative Examples 1 and 2.

[0049] like Figure 3 As shown, the electrochemical impedance test result includes a semicircular area dominated by charge transfer impedance and a diagonal line portion dominated by diffusion. The smaller the radius of the semicircle, the smaller the electrochemical impedance of the electrolyte during the test, and the larger the slope of the diagonal line, the faster the diffusion rate. Comparing the test results of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the performance of the mixed cation electrolyte prepared in Example 1 is significantly better than that of the electrolytes prepared in Comparative Examples 1 and 2.

[0050] Figure 4 It is a performance test diagram of differential capacitance curves in the electrolytes prepared in Example 1 of the present invention and Comparative Examples 1 and 2.

[0051] The larger the value of the vertical axis of the differential capacitance curve is, the higher the capacitance response activity of the carbon cathode material in the electrolyte is, which is beneficial to improving the electrochemical performance at the carbon cathode interface. Figure 4As shown, by comparison, it can be seen that the capacitance response of the cationic mixed electrolyte prepared in Example 1 is much higher than that of the 2M NH4OTF electrolyte prepared in Comparative Example 1 and the 2MZn(OTF)2 electrolyte prepared in Comparative Example 2. The capacitance of the cationic mixed electrolyte prepared in Example 1 ensures the high capacitance response activity at the interface between the carbon cathode and the electrolyte.

[0052] Figure 5 1 is a graph showing the distribution of micelle particle sizes in the electrolytes prepared in Example 1 of the present invention and Comparative Examples 1 and 2.

[0053] like Figure 5 As shown, the 2M NH4OTF electrolyte prepared in Comparative Example 1 has a smaller average micelle size, and the 2M Zn(OTF)2 electrolyte prepared in Comparative Example 2 has a larger ion micelle size. The cationic mixed electrolyte prepared in Example 1 has two ion micelles of different sizes, and its graded solvation structure is beneficial to the reconstruction of the interface Helmholtz layer and the improvement of the pore size utilization of the porous carbon material.

[0054] Figure 6 It is a CV curve performance test diagram of the zinc capacitor in the electrolyte prepared in Example 1 of the present invention and Comparative Example 1 and Comparative Example 2 under the test condition of 2mV / s.

[0055] like Figure 6 As shown, the cationic mixed electrolyte prepared in Example 1 has a larger CV peak area than those in Comparative Example 1 and Comparative Example 2, indicating that under the same test conditions, the mixed cationic electrolyte has a higher current response activity on the carbon cathode surface.

[0056] Figure 7 It is a rate performance test chart of zinc capacitors at 25° C. for the electrolyte prepared in Example 1 of the present invention and the electrolytes prepared in Comparative Examples 1 and 2.

[0057] like Figure 7 As shown, the rate performance test graph uses specific capacity as the ordinate and the abscissa as the number of cycles at different current densities. At the same current density, the greater the value of specific capacity, the better the rate performance of the battery. By comparison, it can be seen that the performance of the zinc capacitor in the mixed cation electrolyte prepared in Example 1 is significantly better than that of the 2M NH4OTF electrolyte prepared in Comparative Example 1 and the 2M Zn(OTF)2 electrolyte prepared in Comparative Example 2, especially the rate performance at high current has been significantly improved.

[0058] Figure 8 This is a test diagram of the cycle performance of a zinc capacitor prepared in Example 1 of the present invention using the electrolyte 1M Zn(OTF)2+1MNH4OTF at a charge and discharge current density of 30A / g.

[0059] like Figure 8 As shown, the cycle performance test graph uses specific capacity as the ordinate and the number of cycles as the abscissa. The more cycles, the higher the capacity retention rate, indicating that the battery has better cycle performance. The cationic electrolyte prepared in Example 1 has excellent cycle performance in the zinc capacitor with graded porous carbon as the cathode, and the capacity retention rate of the assembled zinc capacitor after 400,000 cycles of charge and discharge is 98.59, showing an ultra-long cycle life and stability.

[0060] Functions and Effects of the Embodiments

[0061] The above experimental results show that the aqueous zinc capacitor prepared in Example 1 has an ultra-high cycle life and excellent rate performance.

[0062] The raw materials (zinc trifluoromethanesulfonate, ammonium trifluoromethanesulfonate) used in Example 1 and the comparative example are widely available, low-cost and environmentally friendly. The preparation process of the cationic mixed electrolyte of the zinc capacitor and the aqueous zinc capacitor is simple and easy to operate, and does not involve toxic and harmful reagents or vacuum preparation conditions.

[0063] The hierarchical solvation structure in the cationic mixed electrolyte of the zinc capacitor prepared in Example 1 is beneficial to reconstructing the Helmholtz layer on the cathode and electrolyte surfaces, realizing the redistribution of spatial charge, significantly reducing the interfacial electron and ion transfer impedance, improving the reaction activity and reaction kinetics of the carbon cathode, and storing energy with high energy density and long cycle life.

[0064] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A cationic mixed electrolyte for a zinc capacitor, characterized in that: include: An ammonium salt, a zinc salt and a solvent, wherein the solvent is deionized water.

2. The cationic mixed electrolyte for zinc capacitor according to claim 1, characterized in that: in, The ammonium salt is any one of ammonium trifluoromethanesulfonate, sulfuric acid and ammonium acetate, and the zinc salt is any one of zinc trifluoromethanesulfonate, zinc sulfate and zinc acetate.

3. The cationic mixed electrolyte for zinc capacitor according to claim 1 or 2, characterized in that: in, The concentration of the ammonium salt and the zinc salt in the cationic mixed electrolyte of the zinc capacitor is 0.1-2 mol / L.

4. The cationic mixed electrolyte for zinc capacitor according to claim 1 or 2, characterized in that: in, The molar ratio of the ammonium salt to the zinc salt is 1:5-5:

1.

5. A method for preparing a cationic mixed electrolyte for a zinc capacitor, characterized in that: The method for preparing a cationic mixed electrolyte for a zinc hybrid capacitor according to any one of claims 1 to 4 comprises the following steps: Step 1, weighing a zinc salt and an ammonium salt in a certain molar ratio; Step 2: adding the zinc salt and ammonium salt into water, stirring evenly, ultrasonicating to obtain a clear solution, and letting it stand to obtain the cationic mixed electrolyte of the zinc capacitor.

6. The method for preparing a cationic mixed electrolyte for a zinc capacitor according to claim 5, characterized in that: in, In step 2, the mixing method is ultrasonic for 2 hours, and the standing time is 24 hours.

7. An aqueous zinc capacitor, characterized in that: A cation mixed electrolyte for a zinc capacitor using any one of claims 1 to 4.

8. The aqueous zinc capacitor according to claim 7, characterized in that: in, The positive electrode material of the aqueous zinc hybrid capacitor is a porous carbon material, the negative electrode material is zinc, and the cationic mixed electrolyte is the cationic mixed electrolyte of the zinc capacitor. When the cationic mixed electrolyte of the zinc capacitor is used in the aqueous zinc capacitor, the hierarchical cationic solvation structure induces the Helmholtz plane reconstruction of the carbon cathode surface and thus affects the spatial charge distribution. The synergistic effect of the cationic mixed electrolyte regulates the interface adsorption behavior and electrochemical performance of the zinc capacitor.

9. The aqueous zinc capacitor according to claim 7, characterized in that: in, The cation adsorption behavior on the carbon cathode surface is regulated by adjusting the ratio of the ammonium salt and the zinc salt. The hydrated cations of ammonium have a smaller size than the hydrated cations of zinc. The graded cation mixed electrolyte can regulate the Helmholtz plane of the cathode surface.

Citation Information

Patent Citations

  • Electrolyte and capacitor thereof

    CN117275955A

  • Modified zinc sulfate electrolyte, preparation method and application thereof, and aqueous zinc ion symmetric battery

    CN117558998A

  • Low-temperature aqueous zinc ion hybrid capacitor high-entropy electrolyte

    CN118919313A

  • Electrolyte additives for zinc metal electrodes

    US20200176198A1